Effect of elevated CO2 and temperature on growth and yield of wheat grown in sub-humid climate of eastern Indo-Gangetic Plain (IGP) - PRAKASH , VED; DWIVEDI, S. K.; KUMAR, SANTOSH; MISHRA, J. S.; RAO, K. K.; SINGH, S. S; BHATT, B. P. (MAUSAM, 2017)
The atmospheric CO2 will be in the range of 510 to 760 L-1 by the end of 21st century and mean global temperature will be 1.5 to 4.5 oC higher than the present day which has a direct and indirect effect on agriculture. India is a key global region vulnerable to climate change; however, limited studies have focused on the combine effect of CO2 enrichment and temperature on wheat production in Sub-humid climate of eastern IGP in India. To address this issue, an Open top chamber (OTCs) experiment was conducted during 2013-14, to determine the effects of elevated atmospheric carbon dioxide (CO2) and temperature on growth, yield attributes and yield of wheat. Wheat cultivars (DBW 14 and HD 2967) were grown with four treatment combination of CO2 and temperature in OTCs, during the rabi season. The study revealed that wheat genotypes performed better under elevated CO2 condition in term of grain number, test weight and grain yield than an ambient condition. The greater biomass under elevated CO2 was brought about by an increase in radiation use efficiency (RUE) during both heading and physiological maturity periods. Elevated temperature decreased the grain yield but increase plant height compared to ambient temperature. Days to physiological maturity was reduced by 4 to 7 days in both the cultivars under elevated temperature condition and increased by 3 to 4 days under the elevated CO2 condition with respect to ambient condition. The elevated CO2 had positive effects whereas elevated temperature had negative effects on growth, yield attributes and yield of wheat. With elevation of both CO2 and temperature, elevated CO2 compensate the negative effects of elevated temperature on growth, yield attributes and yield of wheat.